IL-6 inhibition in the treatment of COVID-19: A meta-analysis and meta-regression. Issue 5 (May 2021) - Tharmarajah, Emmanuel; Buazon, April; Patel, Vishit; Hannah, Jennifer R.; Adas, Maryam; Allen, Victoria B.; Bechman, Katie; Clarke, Benjamin D.; Nagra, Deepak; Norton, Sam; Russell, Mark D.; Rutherford, Andrew I.; et al.
Highlights: Multiple RCTs of IL-6 inhibitors in the treatment of COVID-19 have been published, with conflicting conclusions. Our meta-analysis of nine RCTs demonstrated improvements in 28-day mortality in favour of IL-6 inhibition over comparators. Variability across study mortality rates were explained by individual and country-level predictors using meta-regression. These findings support the use of IL-6 inhibitors for the treatment of severe, hospitalised COVID-19. Long-term benefits of IL-6 inhibition and implications for differing standards of care are currently unknown. Summary: Objectives: Multiple RCTs of interleukin-6 (IL-6) inhibitors in COVID-19 have been published, with conflicting conclusions. We performed a meta-analysis to assess the impact of IL-6 inhibition on mortality from COVID-19, utilising meta-regression to explore differences in study results. Methods: Systematic database searches were performed to identify RCTs comparing IL-6 inhibitors (tocilizumab and sarilumab) to placebo or standard of care in adults with COVID-19. Meta-analysis was used to estimate the relative risk of mortality at 28 days between arms, expressed as a risk ratio. Within-study mortality rates were compared, and meta-regression was used to investigate treatment effect modification. Results: Data from nine RCTs were included. The combined mortality rate across studies was 19% (95% CI: 18, 20%), ranging from 2% to 31%. The overall risk ratio for 28-day mortality was 0.90 (95% CI: 0.81, 0.99), in favour of benefit for IL-6 inhibition over placebo or standard of care, with low treatment effect heterogeneity: I 2 0% (95% CI: 0, 53%). Meta-regression showed no evidence of treatment effect modification by patient characteristics. Trial-specific mortality rates were explained by known patient-level predictors of COVID-19 outcome (male sex, CRP, hypertension), and country-level COVID-19 incidence. Conclusions: IL-6 inhibition is associated with clinically meaningful improvements in outcomes for patients admitted with COVID-19. Long-term benefits of IL-6 inhibition, its effectiveness across healthcare systems, and implications for differing standards of care are currently unknown.